“Auditoría tributaria a la librería y papelería Atlántida de la cuidad de Riobamba, durante el periodo 2015 para disminuir el riesgo tributario” - Danny Andrés, Montesdeoca Erazo (2017)
The present research project consists of the application of the Tax Audit to Income Tax, to the Bookstore and Stationery "Atlántida" during the period from January 1, 2015 to December 31, 2015, was carried out with the purpose To analyze compliance with tax obligations in accordance with the provisions of the Organic Law of Internal Tax Regime, its Regulations of Application, as well as other related laws. For the audit we will use techniques and tools that allow us to verify that the tax obligations have been fulfilled, for this we will be based on the information provided by those responsible for said process and the supporting documentation, accounting records and statements with the Purpose of justifying such transactions in order to identify possible errors or tax offenses during the financial period. This project comprises 5 chapters comprised of the following: Reference framework, theoretical framework, methodological framework, processing and discussion of results, conclusions and recommendations. With the aforementioned, it will be announced the economic and tax situation of the bookstore so that it can issue the respective conclusions and recommendations so that the bookstore can accept them as they are based on the legal regulations to which it is subject.